The Role of Psychological Capital in Improving Employee Performance - Gustini; Mulyadi; Azuwandri; Rahmat Alhidayat; M Bima Eka Putra (Journal of Economics and Management, 2025)
Psychological Capital (PsyCap) has increasingly attracted attention as an important psychological resource that can contribute to positive employee outcomes and organizational effectiveness. This study examines the role of Psychological Capital in improving employee performance. Psychological Capital is conceptualized through four core dimensions: self-efficacy, hope, optimism, and resilience, which collectively provide employees with psychological resources to cope with challenges, maintain motivation, and achieve work-related goals. This study employs a quantitative approach using a survey method. Data were collected from employees through structured questionnaires and analyzed using descriptive statistics and inferential analysis to examine the relationship between Psychological Capital and employee performance. The findings indicate that Psychological Capital plays a significant positive role in improving employee performance. Employees with higher levels of self-efficacy, hope, optimism, and resilience tend to demonstrate greater motivation, adaptability, persistence, and effectiveness in completing their tasks. These findings suggest that organizations should pay greater attention to employees' psychological resources through supportive leadership, employee development programs, training, and a positive work environment. Strengthening Psychological Capital can therefore serve as an important managerial strategy for enhancing individual performance and supporting organizational effectiveness. The study contributes to the human resource management literature by emphasizing the importance of positive psychological resources as a strategic factor in achieving sustainable employee performance.